EVALUASI KRITERIA PENILAIAN PEMBELAJARAN BIOLOGI BERBASIS COUNTENANCE - Eka Vasia Anggis (Jurnal Penjaminan Mutu, 2023)
Education directs graduates to achieve the expected graduation so that a measurable assessment is needed based on the criteria set by the government. The purpose of this study was to measure the characteristics of the assessment of biology learning according to predetermined standards. The method used is the countenance evaluation method. The method is in the form of a consideration matrix and a judgment matrix in which there are antecedent, transaction and outcome indicators. The results of this study are that the highest indicator on the criteria for evaluating biology learning is authentic, while the lowest indicator is educative. The conclusion of the research is that the criteria for evaluating biology learning are classified as appropriate according to the standards set by the government.